Analisis Pengaruh Bauran Pemasaran Terhadap Keputusan Pengambilan Kredit Usaha Bagi Nasabah Di Sentra Kredit Kecil PT. BRI (Persero) Cabang Watampone - Idrus, Muhammad; Syam, Marniati (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to influence the marketing mix on business credit decisions for customers in small credit centers of PT. BRI (PERSERO) Watampone Branch. This study was designed based on the objectives to be achieved through a descriptive and associative approach, namely describing descriptively the 7 P's marketing mix and purchasing decisions. Data were analyzed by Multiple Linear Regression Analysis. The results showed that product, price, distribution, promotion, human resources, physical appearance and process simultaneously significantly influence customer decisions in taking credit at BRI Bone Branch. Product, price, distribution, promotion, human resources, physical appearance and process, partially has a significant effect on customer decisions in taking credit at BRI Bone Branch